The Role of Extracurricular Activities in Identifying the Leadership Traits of Secondary School Students in the Negev Region - Hamad, Taleb Ismael Abu (Journal of Posthumanism, 2025)
The study aimed to identify the role of extracurricular activities in determining the leadership traits of secondary school students, as perceived by extracurricular activity coordinators in the Negev region. The study employed both quantitative and qualitative methods through tools such as questionnaires, focus groups, and open interviews. The study population included extracurricular activity coordinators from 43 secondary schools, 9 youth departments, and youth movements and organizations, totaling 443 coordinators. The quantitative sample consisted of a stratified random sample of 301 extracurricular activity coordinators, while the focus group sample included six individuals, and the interview sample comprised 12 supervisors, coordinators, and directors of education and extracurricular activity departments. The results revealed that the arithmetic means for the role of extracurricular activities in identifying leadership traits across the six domains of the questionnaire — democratic expression, learning, creativity and innovation (problem-solving), self-management, confidence-building, decision-making, and communication — were high. The findings also indicated statistically significant differences in the coordinators’ responses regarding the role of extracurricular activities in determining leadership traits in favor of females. The results showed no significant differences in the average scores of coordinators’ responses based on years of service or academic qualifications. However, there were statistically significant differences between the job title "Community Center Coordinator" and "Youth Movement and Organization Coordinator," in favor of the latter.